2014
DOI: 10.1002/widm.1134
|View full text |Cite
|
Sign up to set email alerts
|

Big Data with Cloud Computing: an insight on the computing environment, MapReduce, and programming frameworks

Abstract: The term 'Big Data' has spread rapidly in the framework of Data Mining and Business Intelligence. This new scenario can be defined by means of those problems that cannot be effectively or efficiently addressed using the standard computing resources that we currently have. We must emphasize that Big Data does not just imply large volumes of data but also the necessity for scalability, i.e., to ensure a response in an acceptable elapsed time. When the scalability term is considered, usually traditional parallel-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 194 publications
(114 citation statements)
references
References 128 publications
1
112
0
1
Order By: Relevance
“…A lot of platforms for large-scale processing have tried to meet the challenges of Big Data in the last years [17]. These platforms attempt to carry closer the distributed technologies to the benchmark user (engineers and data scientists) by hiding the technical difficulties derived from distributed environments.…”
Section: Big Data Research Areamentioning
confidence: 99%
“…A lot of platforms for large-scale processing have tried to meet the challenges of Big Data in the last years [17]. These platforms attempt to carry closer the distributed technologies to the benchmark user (engineers and data scientists) by hiding the technical difficulties derived from distributed environments.…”
Section: Big Data Research Areamentioning
confidence: 99%
“…They proposed many alternatives to MapReduce programming model for large scale data processing needs. Madasamy et.al [22] have presented a paper on the performance evaluation of word frequency count in single node and multinode setup under Hadoop environment. They have concluded that multinode configuration yields comparatively better results as the input text file size scales.…”
Section: Literature Surveymentioning
confidence: 99%
“…Nevertheless, considering implementation hazards of the parallel models, scalability can be improved when these models are executed in a cloud within a big data framework as MapReduce [27,28]. This framework guarantees reliability, availability, and a good execution performance in a cloud with a distributed file system.…”
Section: Nâ Nþm ðþmentioning
confidence: 99%